Soil-structure interaction and frequency components of near-fault records on the performance-based confidence levels of steel setback MRFs. Issue 166 (March 2023) - Mashhadi, Sima; Homaei, Farshad
Abstract: This paper investigates the role of soil-structure interaction (SSI) in the confidence levels of setback steel moment-resisting frames (MRFs) for meeting the structural performance objectives, under the action of the components of pulse-like ground motions. To this end, a group of nine flexible-base 10-story steel MRFs with irregular configurations of the setback type, as well as a 10-story regular frame (for comparison purposes) were subjected to the components of 55 near-fault records containing forward directivity pulses. For investigating the role of near- and far-fault shakings, a group of 32 far-fault ground motions was also applied to the structures. The role of soil-structure interaction was considered by using the beam on nonlinear Winkler foundation theory (BNWF) and results were compared with those from the rigid-base frames in the previous study. The pulse components were extracted from the original records through wavelet analysis so that their capability for representing the original near-field excitation would be assessed to impose severe damage on structures. The pulse components were also categorized into four groups according to the pulse-to-structure fundamental period ratio ( T PULSE /T STRUCTURE ). The results reveal that SSI has beneficial and destructive effects on the performance-based confidence levels (PBCL) of all the studied structures under near- and far-fault records, respectively. The detrimental effects of SSI on PBCLs are more obvious for setback frames in comparison with the regular ones. Furthermore, using directivity pulses instead of original near-fault motions does not seem reliable while evaluating the PBCL of flexible-base setback structures, unlike the regular MRFs. Finally, it is highly recommended to consider the T PULSE /T STRUCTURE ratio effects on the PBCL of flexible-base structures, especially for setback frames. Highlights: The role of soil-structure interaction was assessed in the performance-based confidence level of setback special steel moment-resisting frames subjected to frequency components of near-fault records. Uncertainties in the structural performance assessment were accounted for within the probabilistic methods through the demand and capacity factor design (DCFD) approach. The pulse-to-structure period ratio was addressed in the confidence level corresponding to the specific performance objectives of flexible-base buildings. The contribution of forward-directivity pulse records was assessed to the confidence level of meeting a performance objective in flexible-base buildings.